MODEL MEDIASI ADAT HAMUTUK LIA DALAM PENYELESAIAN TINDAK PIDANA PENGEROYOKAN PADA MASYARAKAT ADAT WESEI WEHALI DI DESA FAFOE KABUPATEN MALAKA - Frederikus Yoseph Seran; Karolus Kapong Medan; Bhisa Vitus Wihelminus; Adrianus Djara Dima (PT. Saha Kreasi Indonesia, 2026)
The settlement of criminal acts through customary law mechanisms constitutes part of the living law within Indonesian society. One such practice is the Hamutuk Lia customary mediation model, implemented by the Wesei Wehali indigenous community in Fafoe Village, Malaka Regency, particularly in resolving criminal acts of assault. This study aims to analyze the reasons behind the community’s preference for customary mediation and to examine the mechanism of resolving assault cases through the Hamutuk Lia customary law. This research employs an empirical legal research method with a qualitative approach, conducted through in-depth interviews with customary leaders, offenders, victims, village officials, and local community members. The findings indicate that the Wesei Wehali indigenous community prefers customary mediation because it is considered more affordable, efficient, simple, peace-oriented, and consistent with local customary values. The Hamutuk Lia mediation process involves summoning customary leaders, conducting customary deliberations, determining customary sanctions through the fulfillment of customary obligations, and performing reconciliation rituals aimed at restoring social balance and kinship relations. This mediation model positions customary leaders as mediators and guardians of social harmony, emphasizing restoration and reconciliation rather than punishment. The study concludes that the Hamutuk Lia customary mediation model remains relevant and effective as an alternative mechanism for resolving minor criminal cases within indigenous communities, and it aligns with the state’s recognition of customary law as stipulated in the 1945 Constitution of the Republic of Indonesia and Law Number 6 of 2014 concerning Village.